Oculocutaneous Albinism associated with Axenfeld’s Anomaly : Three case reports - B R Keshav (Sultan Qaboos University Medical Journal, 2010)
Oculocutaneous albinism and anterior mesodermal dysgenesis are well-known heritable conditions, but their occurrence in association has only been rarely reported. We present cases of three siblings of a family with identical presentation suggesting that this association may be more than just a coincidence. This association is worth noting, as this could be one of the causes of ocular morbidity and poor vision in oculocutaneous albinism.